Behavior of spin labels in a variety of interdigitated lipid bilayers. - Boggs, J; Rangaraj, G; Watts, A (1989)
The behavior of a number of spin labels in several lipid bilayers, shown by X-ray diffraction to be interdigitated, has been compared in order to evaluate the ability of the spin label technique to detect and diagnose the structure of lipid bilayers. The main difference between interdigitated and non-interdigitated gel phase bilayers which can be exploited for determination of their structure using spin labels, is that the former have a much less steep fluidity gradient. Thus long chain spin labels with the nitroxide group near the terminal methyl of the chain, such as 16-doxylstearic acid, its methyl ester, or a phosphatidylglycerol spin label containing 16-doxylstearic acid (PG-SL), are more motionally restricted and/or ordered in the interdigitated bilayer than in the non-interdigitated bilayer. This difference is large enough to be of diagnostic value for all three spin labels in the interdigitated bilayers of dihexadecylphosphatidylcholine, dipalmitoylphosphatidylcholine/ethanol, and 1,3-dipalmitoylphosphatidylcholine. However, it is not large enough to be of diagnostic value at low temperatures. Use of probes with the nitroxide group closer to the apolar/polar interface reveals that these latter interdigitated bilayers are more disordered or less closely packed. As the temperature is increased, however, the motion of the PG-SL does not increase as much in these interdigitated bilayers as in non-interdigitated bilayers. The difference in the motion and/or order of PG-SL between interdigitated and non-interdigitated bilayers is large enough at higher temperatures to be of value in diagnosing the structure of the bilayers. Thus by choice of a suitable spin label and a suitable temperature, this technique should prove useful for detection and diagnosis of lipid bilayer structure with a good degree of reliability. Caution must, of course be exercised, as with any spectroscopic technique. Spin labels will also be invaluable for more detailed studies of known interdigitated bilayers, which would be time- and material-consuming, if carried out using X-ray diffraction solely.